2021
DOI: 10.1007/s00192-021-04808-9
|View full text |Cite
|
Sign up to set email alerts
|

North American urogynecology fellowship programs: value of program website content

Abstract: Introduction and hypothesis Urogynecology fellowship program websites are an important source of information to potential applicants, especially given the ongoing COVID-19 pandemic and resulting travel restrictions. Our study evaluated the publicly available information on American and Canadian urogynecology fellowship websites and present recommendations for website content development to promote the subspecialty of urogynecology. Methods Data were collected from all a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…We reviewed colon and rectal surgery fellowship websites to obtain information in the following domains: (1) Program Overview, (2) Application Information, (3) Curriculum, (4) Fellows Information, (5) Alumni Information, (6) Faculty Information, (7) Research, (8) Benefits, and Incentives, (9) Residential Information/Housing Information, (10) Website Update Status. These ten domains were further evaluated by creating a 50-point score (Table 1) based on criteria previously assessed as website content variables in similar studies of different medical specialties [13][14][15][16][17] . If information about specific criteria was available on the fellowship website page or through any of the links of its sub-pages, the criteria were deemed fulfilled and granted a score of 1.…”
Section: Methodsmentioning
confidence: 99%
“…We reviewed colon and rectal surgery fellowship websites to obtain information in the following domains: (1) Program Overview, (2) Application Information, (3) Curriculum, (4) Fellows Information, (5) Alumni Information, (6) Faculty Information, (7) Research, (8) Benefits, and Incentives, (9) Residential Information/Housing Information, (10) Website Update Status. These ten domains were further evaluated by creating a 50-point score (Table 1) based on criteria previously assessed as website content variables in similar studies of different medical specialties [13][14][15][16][17] . If information about specific criteria was available on the fellowship website page or through any of the links of its sub-pages, the criteria were deemed fulfilled and granted a score of 1.…”
Section: Methodsmentioning
confidence: 99%
“…These domains were further delineated into a 40-point criterion ( Table 1 ) based on the variables validated in previous studies to evaluate post-graduate training program websites [ 10 , 11 , 15 , 16 ]. Any data available that was available regarding a specific criterion was given code "1".…”
Section: Methodsmentioning
confidence: 99%
“…Given the ease of access, websites prove to be the most versatile form of information. Therefore, several studies have shown the importance of websites for residency and fellowship applications [ [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] ]. A survey of interventional radiology applicants determined program websites was an even more significant source of information for applicants than contact with residents and physician mentors [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our methodology has been validated in several recent publications [9][10][11]. This study was exempt from institutional review board approval as the data was extracted in its entirety from publicly available resources.…”
Section: Data Collectionmentioning
confidence: 99%